The concept of an ideal society : a review of Fazlur Rahman’s perspective - Abur Hamdi Usman; Mohd. Farid Ravi Abdullah; Muhd. Najib Abdul Kadir; Iskandar, Azwar (Penerbit Universiti Kebangsaan Malaysia, 2022)
The teachings of Islam are closely related to the concept of community. Islamic history and politics influence community structure and organisation based on Quranic tenets. Due to extremism of some Muslim leaders who are still caught in their own orthodoxy, Muslims have been lagging behind the rest of the world in terms of political, economic and social progress. This study examines the philosophy and ideas of Islamic thinker Fazlur Rahman, a modernist scholar and philosopher of Islam. Known as a prominent liberal reformer of Islam, he devoted himself to educational reform and reviving independent reasoning (ijtihad) among Muslims in order to shape an ideal Muslim society. Fazlur Rahman was a unique scholar in that he attempted to combine Islamic and Western elements without compromising the tenets of the Quran and Sunnah in achieving a modern ideal society. He was a liberal in that he believed the Quran was compatible and relevant for all times and human civilisation.